Aid, Policies, and Growth : Revisiting the Evidence - Burnside, Craig (World Bank, Washington, D.C., 2013)
The authors revisit the relationship between aid and growth using a new data set focusing on the 1990s. The evidence supports the view that the impact of aid depends on the quality of state institutions and policies. The authors use an overall measure of institutions and policies popular in the empirical growth literature. The interaction of aid and institutional quality has a robust positive relationship with growth that is strongest in instrumental variable regressions. There is no support for the competing hypothesis that aid has the same positive effect everywhere. The authors also show that in the 1990s the allocation of aid to low-income countries favored those with better institutional quality. This "selectivity" is sensible if aid in fact is more productive in sound institutional and policy environments. The cross-country evidence on aid effectiveness is supported by other types of information as well: case studies, project-level evidence, and opinion polls support the view that corrupt institutions and weak policies limit the impact of financial assistance for development.